Therapeutic processes in group therapy: Intersections between general change mechanisms and motivational stages of change from patient perspective. Issue 3 (3rd July 2018) - Schaller, Georg; Blanck, Paul; Vogel, Eva; Vonderlin, Eva; Bents, Hinrich; Mander, Johannes
ABSTRACT: Intersections between Grawe's General Psychotherapy and Prochaska's Transtheoretical Model were investigated in group therapy in a longitudinal design. It was assumed that general change mechanisms have an impact on patients' stages of change. Specifically, the main hypotheses were that experiential change mechanisms (ECM; clarification of meaning, problem actuation, emotional bond and group cohesion) should be especially relevant for early stages of change (precontemplation and contemplation), whereas behavioral change mechanisms (BCM; resource activation, mastery/coping and task and goals) should be especially relevant for late stages of change (action and maintenance). Therefore, 140 outpatients attending different types of group therapy, with a typical duration of 8 sessions, were investigated. Patients completed the Form for the Evaluation of Therapeutic Processes in Group Therapy (FEPiG), the University of Rhode Island Change Assessment, short version (URICA-S) and several symptomatology measures (BDI-II, BSCL and IIP-32) at two measuring times. Intersections were analysed through correlational analyses, cross-lagged panels and a path-analytic model, supporting the hypotheses. Specifically, results suggested that experiencing ECM at t1 predicted higher levels of reported contemplation at t2. Patients experiencing higher levels of BCM at t1 reported higher levels of action at t2. Clinical implications of the results are discussed.